The Trade Effect of Euro Adoption : An Estimation of the Rose Effect for the Czech Republic - Petržílka, Vítek; Sankot, Ondřej, 1988-; Zeynalov, Ayaz; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
Two decades after committing to replace the Czech koruna with the euro, the issue of euro adoption remains subject to political debate. This thesis aims to evaluate the argument that joining a monetary union has a trade-promoting effect, using data analysis to estimate the impact of euro adoption on Czech trade flows. The analytical tool employed in this thesis is a structural general equilibrium gravity model estimated with Poisson Pseudo-Maximum Likelihood (PPML) estimator. The dataset used for the analysis was created from the International Trade and Production Database for Simulation. The model suggests that euro area membership would reduce international trade costs by approximately 0.5% and increase Czech exports by 5.1%. The effects are overall modest and economically significant for only a few countries. The findings suggest that there is no urgent trade-related reason to adopt the euro. In addition to the quantitative results, the thesis also reviews key characteristics of currency sharing and exchange rate regimes at both the microeconomic and macroeconomic levels.
Vedoucí práce: Ondřej Sankot
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses